Plant Conservation Biology: a view from the Mediterranean ecoregions - Mendoza-Fernández, Antonio Jesús; Salmerón-Sánchez, Esteban; Lorite, Juan; Mota, Juan Francisco; Peñas, Julio (Mediterranean Botany, 2021)
This Special Issue provides an overview of the current status of plant conservation biology in Spain and other regions around the World. Papers represent selected outstanding presentations made during the 9th Congress of the Spanish Society of Plant Conservation Biology, which took place in Granada (Spain) on July 9-12, 2019. These papers cover different topics, all illustrating present trends in plant conservation biology. They highlight the important contribution of different approaches to plant conservation in the area. This special issue is dedicated to the memory of the Spanish botanist José Antonio Fernández Prieto (1950-2019).